Pengaruh Tingkat Perputaran Kas Terhadap Profitabilitas Pada Koperasi Pegawai Republik Indonesia (KPRI) Sumber Makmur - Yanah, Yanah (Exchall, 2019)
Turnover Cash, receivables and inventories as working capital components can affect the short length of time dependent on working capital fund that will ultimately affect the level of profitability achieved. The higher the turnover rate of cash, accounts receivable and inventory indicating the shorter the time dependent capital in the working capital component. This shows the efficiency in the use of capital that would raise the level of profitability achieved KPRI Sumber Makmur. Issues examined in this study were: (1). Is there any influence of cash turnover, accounts receivable and inventories to profitability on Employee Cooperative Republic of Indonesia (KPRI) Sumber Makmur 2002-2004?, (2). How much influence the rate of turnover of cash, receivables and inventories to profitability on Employee Cooperative Republic of Indonesia (KPRI) Sumber Makmur 2002-2004? This study aims to: (1). To determine whether there is influence of the rate of turnover of cash, receivables and inventories to profitability on Employee Cooperative Republic of Indonesia (KPRI) Sumber Makmur years 2002- 2004, and (2). To find out How much influence the rate of turnover of cash, receivables and inventories to profitability on Employee Cooperative Republic of Indonesia (KPRI) Sumber Makmur 2002-2004. The population in this study is KPRI Sumber Makmur years 2002- 2004 which amounted to 46 cooperatives. The sampling technique used was purposive sampling (samples intended). The sample in this study is in the form KPRI Financial Statements Balance Sheet and SHU of twelve (12) KPRI Sumber Makmur for three (3) years ie from 2002 to 2004, so that the sample was 36. There are two variables that were examined in this study, namely: (1). Cash Turnover (X) and (2). Profitability Economy (Y). Data collection tool used in this study is documentation. Analysis of data using multiple linear regression analysis. The results showed that the rate of turnover of cash, accounts receivable and inventory significantly affect the economic profitability KPRI Sumber Makmur amounted to 76.9%. Variable X partially and simultaneously influence the variable Y. Suggestions to convey to the board and managers should KPRI Sumber Makmur is efficiently manage cash sales, both sales of goods and services to members by improving services and providing goods which vary according to the needs and tastes of consumers, the executives and managers KPRI Sumber Makmur should further pursue lending in the short term so that receivables can return within one period. And for the next researcher to pay attention to other factors that may affect the economic profitability.